Subjective vs. objective viewing of "think" in English - Korpal, Paweł (Wydział Anglistyki UAM, 2013)
Subjectivity in language and the process of subjectification have been widely discussed over the last few decades in cognitive grammar. By means of the Langacker’s subjectification theory the author analysed the subjective and objective viewing of the English mental verb think. The present study corroborates the hypothesis that in English the act of thinking is conceptualised mainly in such a way that the speaker is objectified by putting himself on stage.
Keywords: cognitive linguistics; subjectification